Gambaran Riwayat Kontak Penderita TB Paru Anak di Poliklinik Anak Rumah Sakit Umum Cut Meutia - Maulida Sari; Mardiati Mardiati; Nina Herlina (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Tuberculosis (TB) remains a significant health issue in Indonesia, with the number of cases not showing a decline. Pediatric pulmonary tuberculosis is one of the leading causes of morbidity and mortality. In 2018, the number of TB cases in Aceh reached 41,595, with Aceh Utara having the highest number at 4,819 cases, followed by Bireuen with 3,636 cases, while Sabang recorded the lowest at 272 cases. The primary risk factor for pulmonary tuberculosis in children is a history of contact with adult TB patients, as children’s immune systems are still weak, allowing the bacteria to enter their bodies easily. This study aims to examine the history of TB contact in children at the Pediatric Clinic of Cut Meutia General Hospital. The research used a descriptive observational design, with 105 respondents, and data was collected from medical records. The results showed that the majority of respondents were toddlers (47.6%), most were male (54.3%), and 58.1% had good nutritional status. A significant percentage of respondents (77.1%) had a history of contact with TB patients, and 83.8% did not receive BCG vaccination. These findings highlight that contact with TB patients is a key factor in the transmission to children.